Facing the Tides : Managing Capital Flows in Asia - Finger, Harald (Departmental Papers; Departmental Paper ;, 2019)
This paper looks empirically at some economic effects of volatile exchange rates and financial conditions and examines policy responses for managing such volatility. It also sheds light on some economic costs that stem from volatile capital flows and exchange rates and analyzes how countries deploy their policy toolkits in response. The data-driven analysis should contribute to ongoing reflections about how to manage volatile capital flows and exchange rates both in Asian EMEs and more broadly.